Rhizobacterial mediated interactions in Curcuma longa for plant growth and enhanced crop productivity: a systematic review - Khan, Sonam; Ambika,; Rani, Komal; Sharma, Sushant; Kumar, Abhishek; Singh, Seema; Thapliyal, Madhu; Rawat, Pramod; Thakur, Ajay; Pandey, Shailesh; Thapliyal, Ashish; Pal, Manoj; et al. (Frontiers in Plant Science, 2023)
Turmeric (Curcuma longa L.), a significant commercial crop of the Indian subcontinent is widely used as a condiment, natural dye, and as a cure for different ailments. Various bioactive compounds such as turmerones and curcuminoids have been isolated from C. longa that have shown remarkable medicinal activity against various ailments. However, reduced soil fertility, climatic variations, rapid urbanization, and enhanced food demand, pose a multifaceted challenge to the current agricultural practices of C. longa. Plant growth-promoting microbes play a vital role in plant growth and development by regulating primary and secondary metabolite production. Rhizospheric associations are complex species-specific interconnections of different microbiota with a plant that sustain soil health and promote plant growth through nutrient acquisition, nitrogen fixation, phosphate availability, phytohormone production, and antimicrobial activities. An elaborative study of microbiota associated with the roots of C. longa is essential for rhizospheric engineering as there is a huge potential to develop novel products based on microbial consortium formulations and elicitors to improve plant health, stress tolerance, and the production of secondary metabolites such as curcumin. Primarily, the purpose of this review is to implicate the rhizospheric microbial flora as probiotics influencing overall C. longa health, development, and survival for an increase in biomass, enhanced yield of secondary metabolites, and sustainable crop production.